Kinerja, Size, Leverage, dan Pertumbuhan Perusahaan dan Pengungkapan Corporate Social Responsibility Perusahaan Non Keuangan - Surbakti, Manuel Aristo; Wijayanti, Nanda Ayu (E-Jurnal Akuntansi, 2022)
This study aims to determine the effect of company performance, company size, leverage, and company growth on the level of CSR disclosure in non-financial companies listed on the IDX for the period 2016 to 2020. Sampling using purposive sampling, obtained 1,940 research observations. The data analysis technique used panel data regression. The results of the study explain that the company's performance has no effect on CSR. The results also explain that firm size, leverage, and firm growth have an effect on the level of CSR disclosure. These results explain that the level of corporate CSR disclosure can be better when the company has assets and a greater level of leverage, but it shows a lower level of CSR disclosure when the company has higher sales growth. Keywords: Firm Performance; Firm Size; Leverage; Growth; CSR .